INTEGRATION OF MALAY CULTURE IDENTITY WITH ISLAMIC RELIGION - Sohirin Mohammad Solihin (Journal of Malay Islamic Studies, 2017)
Malay culture is the unique racial and ethnic identity of the Malay people that cannot be separated from the teachings of Islam that are embraced by Malay society. This article explains that Malay culture is firmly rooted in Islamic values. The doctrine of the belief in monotheism in Islam is the normative and philosophical basis of Malay culture. Meanwhile the teachings of Islam about truth and justice become the spirit that animates the behavior of the Malay community in their daily lives. Malay culture integrated with Islamic values ​​must be well communicated in the interaction of Malays with non-Malay races and ethnicities. This is important so that the values ​​of Islam as a mercy for the universe can be felt by all humans. The final part of this paper shows how Malay Muslims have not yet understood Malay culture in a broader perspective. Culture is only understood as cultural art, whereas Malay culture also includes aspects of politics, social, science, economics and so on. On the other hand, the behavior of some Malays in these aspects also does not reflect the ideal Malay culture imbued with Islamic values.